Milk protein polymorphisms and casein haplotypes in Blanco Orejinegro cattle of Colombia - Hernandez-Herrera, Darwin Y; Rincon-Florez, Juan C; Pulido-Hoyos M , Maryi N (Revista de Ciências Agroveterinárias, 2024)
The aim was to determine the genetic variation in the CSN1S1, CSN2, CSN1S2, CSN3 and LGB genes in Blanco Orejinegro cattle. 419 animals from 15 herds were genotyped with GGP Bovine 150 K (n= 70) and 50 K (n= 349) chips. Information was obtained from 43 SNPs in the mentioned genes and protein variants *B, *C and *D of αS1-CN; *A1, *A2, *B, *H2 and *F of β-CN; *A and *D of αS2-CN, *A, *A1, *B, *I and *H of κ-CN and *A, *B, *C, *D, *E, *F and *H of β-LG were reconstructed. Allele and genotypic frequencies were estimated for SNPs and for protein variants; Hardy-Weinberg equilibrium and FST values were evaluated for each of the SNPs under different structuring criteria. LD values and haplotypic frequencies were estimated for caseins. The most frequent variants were CSN1S1*B (0.804), CSN2*A2 (0.509), CSN1S2*A (0.997), CSN3*A (0.679) and β-LG*B (0.657). None of the variants showed deviations from HWE, but the CSN2*A2 allele showed a slight increasing trend over time. The FST values were low (0.035) regardless of the structuring criteria. Twenty-eight CSN1S1-CSN2-CSN1S2-CSN3 haplotypes were found, 22 of them with frequencies <5%; the three most frequent were BB-A1A2-AA-AA-AA-AA (16.6%), BB-A1A2-AA-AA-AA-AB (14.1%) and BB-A2A2-AA-AA-AA (10.1%). A good potential of BON cattle to produce high quality milk with functional value was reported.